2016
DOI: 10.4251/wjgo.v8.i1.30
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effects of the benzophenanthridine alkaloid sanguinarine: Evidence and perspectives

Abstract: Historically, natural products have represented a significant source of anticancer agents, with plant-derived drugs becoming increasingly explored. In particular, sanguinarine is a benzophenanthridine alkaloid obtained from the root of Sanguinaria canadensis , and from other poppy Fumaria species, with recognized anti-microbial, anti-oxidant and anti-inflammatory properties. Recently, increasing evidence that sanguinarine exibits anticancer potential through its capability of inducing apoptosis and/or antiprol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 98 publications
3
53
0
Order By: Relevance
“…However, if the production of sanguinarine is inducible by various exogenous elicitors that mimic the pathogen attack (biotic elicitation), the production of macarpine in intact plants or cell cultures of natural producers is also increased. Recent studies have revealed the prospective biological activities of macarpine toward cancer cells [12,14,24], but extensive testing is limited by its availability from natural sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the production of sanguinarine is inducible by various exogenous elicitors that mimic the pathogen attack (biotic elicitation), the production of macarpine in intact plants or cell cultures of natural producers is also increased. Recent studies have revealed the prospective biological activities of macarpine toward cancer cells [12,14,24], but extensive testing is limited by its availability from natural sources.…”
Section: Discussionmentioning
confidence: 99%
“…In general, quaternary benzophenanthridine alkaloids possess a broad spectrum of biological activities, including anti-bacterial, anti-viral, anti-oxidative, anti-inflammatory and neuroprotective properties [9][10][11]. Recently, the strong antiproliferative and apoptotic effects of sanguinarine, chelerythrine, macarpine and chelirubine against a broad spectrum of human cancer cell lines have been identified, which predetermine their use as an adjuvants in cancer therapy [12][13][14]. Besides the mentioned activities, macarpine evinces an ability to interact with DNA and its fluorescence properties could be used as a DNA probe for fluorescence microscopy and flow cytometry including analyses of the cell cycle [1].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, other studies report concerns of toxicity linked to increased risks of oral leukoplakia, questioning safety of the use of this compound in dental care products (Maskarenhas et al, 2002). Sanguinarine also appears to exert interesting anticancer activities, playing a crucial role in various steps of tumor cell development and metastases (Gaziano et al, 2016). Furthermore, this compound has been incorporated into food additives to promote animal growth, exhibiting properties that are of veterinary relevance (Kosina et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of literature data underlines the promising therapeutic importance of sanguinarine (Gaziano et al, 2016), there is only limited information about the effects of this alkaloid during embryonic development (Chan, 2014). Application of these results to clinical practice requires further in vivo studies to define its possible effects on developing organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on sanguinarine have documented a wide spectrum of therapeutic properties, including anti-microbial [Miao et al, 2011;Yang et al, 2012], anti-inflammatory [Niu et al, 2012;Li et al, 2014], antioxidative [Firatli et al, 1994;Vrba et al, 2004], immunomodulatory [Senchina et al, 2009;Vlachojannis et al, 2012] and anti-angiogenic [Eun and Koh, 2004;Basini et al, 2007] effects. Sanguinarine has also demonstrated anti-cancer activities, due to its ability to inhibit cell growth or to induce cell cycle arrest and apoptotic pathways in distinct cancer cell types [Gupta et al, 2010;Gaziano et al, 2016]. Interestingly, this agent does not show any apoptotic effects on normal cells, making it highly promising as an anticancer drug [Ahmad et al, 2000].…”
Section: Introductionmentioning
confidence: 99%